Optimal Arrangement Strategy of IoT Sensors in Urban Drainage Networks: A Review - Yiyi Ma; Tianyu Guo; Yiran Wang (Applied Sciences)
The Urban Drainage Network (UDN) is a type of underground municipal infrastructure responsible for transporting sewage and rainwater. To keep abreast of the hydraulic and water quality conditions of the pipes and to detect problems such as pipe clogging, pollution and leakage, real-time monitoring sensors have been widely adopted, accomplished with the development of IoT technologies. However, the intricate topology and numerous nodes of drainage pipes complicate IoT sensor placement strategies, especially in the selection of sensors and the location of monitoring points. This review examines application cases of IoT sensors in UDNs and some other hydraulic networks, evaluating the characteristics and applicability of various optimal placement methods and theories. A general framework was proposed applicable to the optimal placement of IoT sensors in the UDN, including object classification–method selection–quantitative evaluation. Currently, the quantitative evaluation of monitoring schemes lacks a systematic process, and existing layout methods may not be optimal. Future research can explore dynamic optimization strategies through phased deployment and feedback iteration, which can enhance the accuracy and objectivity of sensor layout design and evaluation.